Development of an algorithm for raw materials group composition calculation in a vacuum gas oil hydrotreating mathematical model; Химия и химическая технология в XXI веке; Т. 2 - Arkenova S. B. Sania Bolatovna (Химия и химическая технология на иностранном языке (английский), 2021)
Заглавие с титульного экрана